Five new species of Nototriche sect. Nototriche (Malvoideae, Malvaceae) from the Peruvian high Andes - Mazzei, Piero; Batalla, Martín I.; Montesinos-Tubée, Daniel B.; Gonzáles, Paúl; Cano, Asunción (Phytotaxa, 2025)
As a part of a larger taxonomic revision of Nototriche, five new species from the Peruvian Andes are described: Nototriche ancashensis, N. bicentenaria, N. chambii, N. heroica and N. latorreae. Descriptions, illustrations, and photographs of the new species are included, as well as a dichotomous key for the species of Nototriche sect. Nototriche occurring in Peru.